2020
DOI: 10.1007/s42452-020-2654-y
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent hybrid approaches for ensuring better prediction of gas-assisted EDM responses

Abstract: The present research work explores the implementation of three smart hybrid predictive models based on the adaptive neuro-fuzzy inference system (ANFIS), ANFIS and genetic algorithm (GA), and ANFIS and particle swarm optimization (PSO). All such strategies have been used to determine and compare machining key elements including material removal rate (MRR) and surface roughness (SR) during the gas-assisted electrical discharge (GAEDM) process. In this study, inert gas-based EDM with a multi-hole rotating tool h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…and [32] with the addition of four spin coupling , direct spin-spin interaction term, indirect spin -lattice interactions, phonon anharmonic interactions up to quartic, as well as extra interaction terms. The contribution of these extra interaction terms clearly found in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and [32] with the addition of four spin coupling , direct spin-spin interaction term, indirect spin -lattice interactions, phonon anharmonic interactions up to quartic, as well as extra interaction terms. The contribution of these extra interaction terms clearly found in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…and 𝐽 ′ = 7𝐽 3 , but they have not studied advanced ferroelectric properties like frequency response function, polarization and permittivity. Pawan and Upadhyay [32] have also studied these crystals with the help of the PLCM model, but they have not introduced the extra interaction terms which we have considered and the proper decoupling scheme. These terms enhance the rigours results in our calculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal input values (process parameters) for different desired SR were obtained, and the variation of SR and MRR were heavily dependent on discharge energy fluctuation. Singh et al [68] proposed an intelligent hybrid approach, using the PSO algorithm, to obtain a desired prediction of gas-assisted EDM (GA-EDM) performance. The results showed that the improved PSO algorithm was effective for the G-EDM performance estimation.…”
Section: Single-objective Optimizationmentioning
confidence: 99%